Pengaruh Etika Kerja Islami dan Kualitas Pelayanan Pedagang terhadap Kepuasan Pelanggan di Pasar PON Jombang - Difa Azzahrowani, Ilma; Rachma Indrarini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The market is a certain place for the meeting of people who carry out trading activities (buying and selling) of goods and services. Jombang is an area that has the nickname as